Reliability Analysis of 3 Phase Generator Set as An Emergency Power Supply If There are Electricity Outages at PT. Intracawood Manufacturing - Musmuliadi; Mado, Ismit; Budiman, Achmad; Subarianto; Rantepadang, Agustinus (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
The need for electricity is a problem that occurs every year, especially in environments that really need a very high supply of electricity, such as companies, industries, offices, and lecture buildings. To maintain the continuity of the supply of electrical energy in the event of a disturbance, it is necessary to back up the generating system. As with the operation of a power generation system, it is also necessary to maintain the continuity and reliability of this backup power plant. To determine the level of reliability and availability, equipment data, operational data and damage data are needed. This study calculates the specified operating time (SOT), the total number of damages and the number of generators that are not operated due to routine or scheduled maintenance needs. calculating maintenance hours (S) and total maintenance time for each generator within a predetermined period. From SOT minus the total maintenance time, you will get the actual operating time (AOT) value of each generator. SOT and AOT data are needed to calculate the level of availability of generators individually and the level of availability of generators as a backup power supply. Furthermore, this research calculates the mean time between failure (MTBF) for each generator. The results of the study show that in 2022 the reliability level of PT. Intracawood Manufacturing by 99%. The generator set reliability level is included in the group that rarely experiences disturbances or damage (R≥ 90%) and the average generator set availability rate in 2022 is 98.5%. This study shows that the operating target of the power generation system at PT. Intracawood Manufacturing rarely experiences interruptions.